The Solution of a Few Infinite Problems in the Mathematics - Zhang Yue (Budapest International Research and Critics University, 2023)
Many infinite mathematics problems take a lot of work for people, including myself, to deal with. The paper discusses a few typical infinite problems in mathematics, and it calculates out the sum of the infinite layers of the square root of 2; it calculates out the result of the problem consisting of the infinite power of; it demonstrates how to deal with the problem of the infinite decimal; it calculates out the result of the infinite continued fraction; it calculates out the result of the problem consisting of the multiplication by infinite layers of. The paper presents a method of solution commonly useful for most of the infinite problems in mathematics.